Market information feedback for the high-tech dominated IPO companies. (14th July 2008) - Shih, Kuang-Hsun; Lin, Ching-Wen; Huang, Huang-Ta; Chiang, Wen-Chyuan
The prevalence of investment opportunities and the cost of capital are the two uncertainties that affect the managers' selection and judgment of future investment opportunities. This study investigates the effect of an IPO company's initial return on the investment policies of managers by examining the causal relationships among variables including pre- and post-IPO capital expenditure levels, forecasted growth rates, company size and initial returns. The findings show Market Feedback Hypothesis, which applies to Taiwan's market, but also managers take advantage of their control of pre-IPO investment and dividend policies to influence the judgment of investors at the time of the initial public offering in order to affect the initial return rate. In addition, company size has an inverse relationship to the stability of both pre- and post-IPO investment policies: smaller companies' managers tend to refer to investors' expectations when adjusting their future investment policies.